Pengaruh Leverage, Profitabilitas, Dan Persistensi Laba Untuk Konservatisme Akuntansi Dalam Perusahaan Sektor Transportasi Serta Logistik Yang Tercatat Dalam Bei Periode 2019 – 2023 - Hesti Nuraini; Lilik Ambarwati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research investigates the impact of leverage, profitability, and earnings persistence on accounting conservatism within transportation and logistics firms listed on the Indonesia Stock Exchange (IDX) over the period from 2019 to 2023. Utilizing a quantitative approach, the study analyzes secondary data from 25 companies selected through purposive sampling. The data analysis involved descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination, employing SPSS version 25 for computations.The results from the t-tests reveal that the leverage variable has a significance level of 0.000, which is below the threshold of 0.05. Similarly, profitability also presents a significance level of 0.000, and earnings persistence mirrors this with a significance level of 0.000 as well. Consequently, the findings indicate that all three factors leverage, profitability, and earnings persistence positively and significantly influence accounting conservatism, both individually and collectively. This study offers empirical insights into the determinants affecting accounting conservatism in Indonesian transportation and logistics companies, providing valuable information for investors, management, and other stakeholders involved in financial decision-making.